Oral health in older adults with cancer - Ana Patricia Navarrete-Reyes; Juan Pablo Negrete-Najar; Gabriel Cojuc-Konigsberg; Jimena Gómez-Camacho; Yoselin Juárez-Carrillo; Luis Gerardo López-Mosqueda; Rodrigo Rangel-Tapia; Juan Alberto Ríos-Nava; Carlos Alberto Ruiz-Manríquez; Darío Alejandro Sandoval-Valdez; Ana Cristina Torres-Pérez; Juan Miguel Antonio García-Lara; et al. (Brazilian Society of Geriatrics and Gerontology, 2023)
Cancer is a disease of older adults, with 60% of cancer diagnoses and 70% of cancer deaths occurring in individuals ≥ 65 years. Normal oral aging may transition to disease in the presence of one or more potential modifiers, such as a new oncological diagnosis or a new treatment. Oral conditions in patients with cancer cause significant morbidity. Previous work suggests that oral conditions are neither elicited/assessed/reassessed nor well-managed or investigated in older patients. However, frequently reported oral conditions in patients undergoing cancer therapy include xerostomia, dysgeusia, candidiasis, mucositis, and dental caries. Some oncological treatments such as hematopoietic stem cell transplant or chemotherapy/radiotherapy for head and neck cancers entail higher risks of oral complications. No specific recommendations in the case of older adults with cancer-associated oral conditions are available. Treatment recommendations are based on low levels of evidence and/or evidence extrapolated from younger patients with cancer.